Sedentary time is related to deficits in response inhibition among adults with overweight and obesity: An accelerometry and event‐related brain potentials study. (22nd May 2021) - Pindus, Dominika M.; Edwards, Caitlyn G.; Walk, Anne M.; Reeser, Ginger; Burd, Nicholas A.; Holscher, Hannah D.; Khan, Naiman A.
Abstract: Excessive sedentariness has been related to poorer cognitive control in adults. Sedentariness may compound obesity‐related impairments in response inhibition, but its relationship to response inhibition remains poorly understood. This study investigated the relationship between accelerometer‐measured sedentary time (ST, min/day), performance on the Oddball and NoGo tasks, N2 and P3‐ERP indices of response inhibition and attentional control in 80 adults with overweight and obesity (55 females, M age = 35.2 ± 5.8 years, BMI = 32.8 ± 5.3 kg/m 2 ). ST was not related to performance on the Oddball task. However, more sedentary adults had larger P3b amplitude to targets. Higher ST was also related to increased attentional resource allocation during NoGo target and nontarget trials as indicated by higher P3b amplitudes across centroparietal sites (C1, Cz, C2, CP1, CPz, CP2; p s ≤ .03). ST was negatively indirectly related to target accuracy on NoGo trials through its association with faster response times to nontargets (95% percentile bootstrap CI for a standardized effect: −0.182, −0.014). ST was not related to N2 amplitude on either Oddball or NoGo target trials. Adjustment for moderate‐to‐vigorous physical activity (MVPA; all models), age (models with P3b NoGo target amplitude, N2 NoGo target amplitude and latency), and % fat mass (models with target NoGo accuracy and N2 NoGo target amplitude) did not modulate behavioral findings. MVPA did not significantly predict P3b amplitude. Our results suggest suboptimal response inhibition due to trading accuracy for speed and despite the upregulation of attentional resources among more sedentary adults with overweight and obesity. Abstract : Our findings add a new dimension implicating higher sedentary time (ST) in subtle reductions in response inhibition among adults with overweight and obesity. Our study adds to previous research by showing that a deficit in response inhibition was mediated by faster responses to go trials. Decreased response inhibition with higher ST coincided with increased allocation of attentional resources throughout the task as indicated by larger P3b amplitudes.